Sustainable Tourism in 2024: The Role of Tourists and Industry in Preserving Marine Nature - Prihadi, Donny Juliandri; Dhahiyat, Ahmad Prawira; Kristiadhi, Fanny; Pamungkas, Wahyuniar (MSJ : Majority Science Journal, 2024)
In 2024, sustainable tourism will become the main focus of the global tourism industry, especially in preserving marine nature that is vulnerable to environmental damage. Marine tourism, such as diving and snorkeling, is increasingly popular, but also poses a threat to marine ecosystems. These tourism activities have had serious impacts on coral reefs, fish populations, and seawater quality. Therefore, a collaborative strategy is needed between tourists and the industry to create a balanced positive impact. The tourism industry is required to introduce environmentally friendly tourism practices, while tourists need to be educated to be aware of the impact of their activities on the environment. This study aims to identify the role of tourists and industry in preserving the ocean through sustainable tourism practices in Indonesia. This study uses a Systematic Literature Review (SLR) approach to examine scientific studies and relevant practices in sustainable marine tourism management. Based on the results of the analysis, it was found that collaboration between tourists, industry, and government can increase the effectiveness of marine conservation. On the other hand, there are challenges related to implementation costs, as well as public understanding of the importance of a healthy marine ecosystem. Therefore, increasing public awareness and strong policy support are important to ensure the sustainability of the tourism sector and the sustainability of the marine environment in Indonesia.